Changing Perceptions About Feminists and (Still Not) Claiming a Feminist Identity - Dyer, S; Hurd, F (Routledge, 2016)
We examine student perceptions about feminists and feminism, and the willingness to claim a feminist identity and engage in collective activism, as stated at the beginning and end of a Women’s Studies course. Course participation simultaneously fostered more positive views towards feminists and feminism and entrenched the unwillingness to claim a feminist identity and engage in activism. These contradictory outcomes stemmed from the critical capacity to recognise that structural inequality is reproduced through disciplinary relationships. Thus, unwillingness was entangled with feelings of fear and vulnerability in relation to the national context whereby neoliberalism guides the governance of the self, and where gender equality has presumed to be achieved. The article highlights that developing the willingness to identify and act is intimately shaped and constrained by the socio-political context and personal relationships. We consider the implications of this insight in relation to pedagogical assumptions about developing feminist knowledge in the classroom.
Keywords: Feminist identity; Feminist knowledge; Pedagogy; Structural inequality